Analisis Kinerja Inkubator Bisnis Dalam Pendampingan Usaha Tenant - Agus Dwi Atmoko (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2021)
Presidential Regulation No. 27 of 2013 on Small Business Incubator Development define an incubator business as an institution that gives their business assistance to their tenants. The aims of this research is to assess perfomance of business and technology incubator in mentoring business tenant. The research was held in business and technology incubator of Politeknik Sawunggalih Aji and done by interviewing manager and tenants incubator. The type of research used is a quantitative descriptive. The source obtained was analyzed by a method balanced scorecard (BSC). The research finding show, the score of performance achievement of "Inkubator Bisnis Politeknik Sawunggalih Aji " is 48.528. According to Price Waterhouse Coopers in the tenant business partnering, shows that "Inkubator Bisnis Politeknik Sawunggalih Aji " needs more efforts. "Inkubator Bisnis Politeknik Sawunggalih Aji " has already contributed in developing the performance of tenant business, especially increasing of the turnover, the quantity of labor, the production capacity, and the access to the capital resources. "Inkubator Bisnis Politeknik Sawunggalih Aji " needs to increase its performance by many ways, such as improving incubator management aspect also adding some competent executives and partners. Beside that government can socialize the role of business incubator in the tenant business partnership, so the society can take advantage of the business incubator facility wisely.